Human cancer risk and exposure to 1,3-butadiene - a tale of mice and men - Stayner, LT; Dankovic, DA; Smith, RJ; Gilbert, SJ; Bailer, AJ (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'The purpose of this study was to evaluate empirically the relevance of animal-bioassay-based models for predicting human risks from exposure to 1,3-butadiene (BD) using epidemiologic data.' ' METHODS ': 'Relative-risk results obtained with a regression model in a recent epidemiologic study were used to estimate leukemia risk for occupational and environmental exposures to BD and to compare these estimates with those previously derived from an analysis of animal bioassay data.' ' RESULTS ': 'The estimates of risk were found to be highly dependent on the model used when low levels of exposure were evaluated that are of environmental concern, but not at the levels of occupational concern. For example, at the level (1 part per million) of the recently revised standard of the Occupational Safety and Health Administration in the United States the estimates of lifetime excess risk ranged from 1 to 8 per 1000 workers. The range of the risk estimates derived from the epidemiologic models was remarkably similar to the range of risk estimates for occupational exposures (1 to 9 per thousand) previously developed by Dankovic et al in 1993 from an analysis of a mouse bioassay study for lymphocytic lymphoma.' ' CONCLUSIONS ': 'Results for BD seem to provide another example of a high degree of concordance between the risk predictions from models of toxicologic and epidemiologic data, particularly at occupational levels of exposure.
Keywords: epidemiology; leukemia; risk assessment; toxicology